Willy Aureli e a Bandeira Piratininga : expedições, imprensa e literatura (1937-1968) - Kurtz, Leonardo Birnfeld (2023)
Willy Aureli (1898-1968) was a journalist, writer, sertanista and indigenist from the state of São Paulo who created and led the Bandeira Piratininga, a private expeditionary group, from 1937-1959. This Bandeira traveled to the region between the rivers Araguaia and Mortes in five different occasions, aiming to reach geographic landmarks, map rivers and contact indigenous people in the region, especially Carajás, Caiapós, Tapirapés and Xavantes. The group was a private endeavor whose financing depended on São Paulo’s citizens, companies, publishers and newspapers. Its activities, even though they were private, synchronized with the objectives of the Marcha para o Oeste. Despite that, the Bandeira’s trajectory was a target for the criticism that came from state-related authorities, journalists, scientists and missionaries. Those critiques constantly obligated Aureli to make concessions, negotiate and defend himself in the press and in his books. Therefore, Willy and his Bandeira participated in a field of dispute whose different agents competed over the supremacy of a way to contact indigenous people, explore nature and produce knowledge. Through Aureli’s literary work, analyzing 8 of his 10 books, and the press, researching news connected with the Bandeira Piratininga inside the archives of O Globo, Folha de São Paulo and Hemeroteca Digital between 1937-2022, it was possible to thoroughly describe the 1937 and 1938 expeditions and analyze how Aureli positioned himself within the indigenist field. The first two incursions can be seen as formative moments for the Piratininga which helped to identify the participants, financing, objectives and itineraries. The analysis of the way Aureli constituted himself within discourse, as well as when he dealt with other, resulted in the identification of a series of tendencies and eventual changes in his form of describing nature, indigenous people, sertanejos, state agents and christian missions that operated in the explored region. Throughout his life and work, Willy tried to constitute himself as a believable observer of the sertão, whose basis of credibility resided in his empirical experience of the place, in opposition to scholars or indigenist agents that demonstrated cynicism towards the results and actions of the Piratininga.